Financing Constraints, Home Equity and Selection into Entrepreneurship - Thais Laerkholm Jensen; Søren Leth-Petersen; Ramana Nanda (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2021)
We exploit a mortgage reform that differentially unlocked home equity across the Danish population and study how this impacted selection into entrepreneurship. We find that increased entry was concentrated among entrepreneurs whose firms were founded in industries where they had no prior work experience. In addition, we find that marginal entrants benefiting from the reform had higher pre-entry earnings and that a significant share of entrants started longer-lasting firms. Our results are most consistent with the view that housing collateral enabled high ability individuals with less-well-established track records to overcome credit rationing and start new firms, rather than just leading to `frivolous entry' by those without prior industry experience.
Keywords: D14; D31; G21; L25; L26; 330; credit constraints; entrepreneurship; household wealth; mortgage finance